Otonomi Daerah dan Perkembangan “Peraturan-Peraturan Daerah Bernuansa Syari’ah” - Muntoha Muntoha (Jurnal Hukum IUS QUIA IUSTUM, 2008)
The central government policy which granted the autonomy for some local governments has brought about the rise of local regulations which are drafted in accordance with the local aspirations. Accordingly, for the residences where their socio-historical backgrounds are marked with Islamic tradition, tends to aggregate Islamic values in the regulations they issue.